Rāingān kh̨̄ong Khana Kammāthikān Kānkasēt læ Sahak̨̄on, Wutthi Saphā, sūan thī 3, phitčhāranā sưksā r̄ưang kānčhatkān sapphayāk̨̄on pāmai dōi chumchon ph̄ưa ʻanurak pā tonnam, lamthān (K̨̄ong Kammāthikān, Samnakngān Lēkhāthikān Wutthi Saphā, 1997)
Report on forest conservation by the local communities.